Anti-reflective structures for photovoltaics: Numerical and experimental design - Kuan W. A. Chee; Ziqiang Tang; Hong Lü; Feng Huang (Energy Reports, 2018)
The effects of different anti-reflective structures on the photovoltaic performance of the silicon solar cell were studied using finite-element modelling and numerical simulations for which experiment alone does not provide a full description. The front surface reflectivity may be mitigated significantly by an anti-reflective coating (ARC) of a suitable thickness. Alternatively, nanoscale surface texturing can effectively trap a greater ratio of incident light to increase optical absorption. The optimized layer thicknesses of the ZnO single layer and SiO2/Si3N4 double layer films were calculated for minimum reflectivity, with the former grown by magnetron sputter deposition and characterized using specular X-ray reflectivity measurements. Based on geometric ray-tracing and solutions to the semiconductor equations, the theoretical photovoltaic performance was simulated and compared for a range of incident angles at an optical intensity of 0.1 Wcm-2, revealing a limit to the angular collection efficiency of the ARC at a grazing incidence angle of 30ê. Using ZnO or SiO2/Si3N4 ARCs or surface texturing increases the power conversion efficiency by 20%, 24% and 30% respectively at normal incidence. The insights provided by physical-based modelling on the optimized design parameters of the anti-reflective structures confer a promising pathway for enhancing the external quantum efficiency of photovoltaic devices.
Keywords: 330; Energy conversion; Photovoltaic cells; Reflectivity; Surface engineering; Thin films